2018
DOI: 10.18535/ijsrm/v6i8.c01
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS analysis of raw and roasted seeds of Chrysophyllum albidum, a medicinal plant used for the treatment of tuberculosis

Abstract: Tuberculosis is a multi-systematic disease with myriad presentations and manifestations and is the most common cause of infectious disease-related mortality worldwide. The disease is treated with the roasted cotyledonous part of Chrysophyllum albidum seeds by traditional practitioners in Ogun state, Nigeria. The phytoconstituents of the hexane fraction and the hexane extracts of the roasted seeds at 50o C, 100o C and 120o C were investigated using GC-MS analysis. The results showed the hexane fraction of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In particular, the stem-bark explored in this study has been reported in literature as a remedy for malaria and yellow fever [16,9,11,12,15]. In our laboratory, earlier investigations of the antimicrobial constituents of Chrysophllum albidum seed cotyledons led to the isolation and characterization of three alkaloids viz: eleaginine, tetrahydro-2methylharman and skatole [7] and from the stem-bark, stigmasterol, epicatechin, epigallocatechin and procyanidin B5 [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In particular, the stem-bark explored in this study has been reported in literature as a remedy for malaria and yellow fever [16,9,11,12,15]. In our laboratory, earlier investigations of the antimicrobial constituents of Chrysophllum albidum seed cotyledons led to the isolation and characterization of three alkaloids viz: eleaginine, tetrahydro-2methylharman and skatole [7] and from the stem-bark, stigmasterol, epicatechin, epigallocatechin and procyanidin B5 [17].…”
Section: Introductionmentioning
confidence: 94%
“…In the last two decades, various researchers have subjected the plant, Chrysophyllum albidum to phytochemical, pharmacological and clinical studies and it has been reported to have several biological activities. [7,8,9,10,1,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%